2003
DOI: 10.1108/00346650310488499
|View full text |Cite
|
Sign up to set email alerts
|

Reasons behind consumers’ functional food choices

Abstract: The aim of this study was to examine what reasons consumers give for either choosing or not choosing functional foods. Laddering interviews were used to find out how consumers described their reasons for choosing functional food alternatives in different product categories and how these descriptions are linked with values. Yoghurt, spread, juice, carbonated soft drinks, sweets and ice cream were used as example product categories. In total, five central means-end chains, describing the product attributes, cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
137
2
16

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(173 citation statements)
references
References 13 publications
18
137
2
16
Order By: Relevance
“…The behaviour of functional foods consumption was influenced by demographic factors that contribute to attitudes and behaviours of acceptance of functional foods (Gilbert, 2000;Bech-Larsen & Grunert, 2003;Urala & Lähteenmäki, 2003;. Sääksjärvi et al (2009) stated that consumers with high-income level affected the high consumption of functional foods.…”
Section: Introductionmentioning
confidence: 99%
“…The behaviour of functional foods consumption was influenced by demographic factors that contribute to attitudes and behaviours of acceptance of functional foods (Gilbert, 2000;Bech-Larsen & Grunert, 2003;Urala & Lähteenmäki, 2003;. Sääksjärvi et al (2009) stated that consumers with high-income level affected the high consumption of functional foods.…”
Section: Introductionmentioning
confidence: 99%
“…Consumer research has so far mainly focused on consumer beliefs and attitudes of the functional food consumer. Several dimensions were found to describe consumers' attitudes towards functional foods: healthiness, taste, pleasure, security and familiarity (Urala and Lahteenmaki, 2004;Urala et al, 2003;Poulsen, 1999). Studies confirmed the importance of 'knowledge' when choosing functional foods (Verbeke, 2005), but socio-demographic factors were also found to be important determinants.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the use of voluntarily fortified foods may not always be a conscious choice so much as a result of the fact that non-fortified options are few or not available at all in the store. The choice of a fortified product may also Table 1 The total amount of voluntarily fortified food purchased, by food group and added nutrient, among random subgroup of 918 adult participants (aged 25-64 years) in the National be based on attributes other than fortification, such as taste, familiarity, convenience and price (8) . Ready-to-eat breakfast cereals are the most commonly used voluntarily fortified foods worldwide (9)(10)(11)(12) .…”
Section: Discussionmentioning
confidence: 99%